Comparing the Association Between Depressive Symptoms and Cardiovascular Disease Among the Middle-Aged and Elderly Population: A National Survey of 9,049 Subjects Based on the Indonesian Family Life Survey-5 - Alfian SD; Permata PGR; Griselda M; Puspitasari IM; Abdulah R (Vascular Health and Risk Management)
Sofa D Alfian,1– 3 Putri GR Permata,1 Meliana Griselda,2 Irma Melyani Puspitasari,1,2 Rizky Abdulah1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, Indonesia; 3Center for Health Technology Assessment, Universitas Padjadjaran, Jatinangor, IndonesiaCorrespondence: Sofa D Alfian, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, West Java, Indonesia, Tel +62 22 84288888, Email sofa.alfian@unpad.ac.idIntroduction: The association between depressive symptoms and cardiovascular disease (CVD) is widely acknowledged. However, there is a lack of relevant evidence among the middle-aged population in developing countries where depressive symptoms often go undetected and untreated. The objectives of this study were to assess the association between depressive symptoms and CVD in Indonesia and to compare the association between the middle-aged and elderly population.Methods: This national cross-sectional population-based survey used secondary data from the publicly available Indonesian Family Life Survey (IFLS-5). Depressive symptoms were assessed using a modified Center for Epidemiologic Studies Depression (CESD-R-10) scale, and data on CVD and sociodemographic variables were self-reported. Binary logistic regression was performed to determine the association between depressive symptom and self-reported CVD after adjusting for confounding factors, with an adjusted odds ratio (AOR) and 95% confidence interval (CI) reported. Subgroup analysis was performed based on the age group.Results: The study included 9049 respondents, predominantly the middle-aged (71.1%), female (52.6%), elementary school graduates (50.7%), non-smokers (59.0%), non-obese (77.3%), without depressive symptoms (82.2%), and without self-reported CVD (96.7%). Respondents with depressive symptoms were more likely to experience self-reported CVD (AOR = 1.56; 95% CI = 1.18– 2.05; p-value = 0.002), after adjusting for potential confounders. A significant association was observed between depressive symptoms and self-reported CVD in elderly respondents (AOR = 1.89; 95% CI = 1.22– 2.94; p-value = 0.005), whereas no significant association was observed in the middle-aged group (AOR = 1.39; 95% CI = 0.98– 1.98; p-value = 0.063) after adjusting for confounders.Conclusion: Respondents with depressive symptoms were associated with an increased risk of self-reported CVD, highlighting the urgent need for targeted prevention strategies, especially for those struggling with depressive symptoms. Keywords: depression, cardiovascular disease, middle-age, elderly, IFLS-5